Protection of Personal Data in the Context of the Parochial Vicar Online Activities - Kroczek, Piotr (Prawo Kanoniczne, 2025)
The article addresses the issue of the canonical liability of a parochial vicar for publishing content containing personal data on the Internet. The purpose of the research was to determine the normative sources of potential liability and to identify possible exemptions from such liability. The analysis showed that a parochial vicar’s activities involving the processing of personal data online may fall within the scope of the 2018 General Decree on the protection of personal data in the Church in Poland, despite the decree’s literal restriction of subject scope to ecclesiastical legal persons. The article also identifies grounds for excluding the application of data protection regulations in cases of activities of a private nature. The author calls for strengthening measures reminding clergy of their obligation to comply with data protection regulations, as well as increasing canonical supervision of such activities by parochial vicars.